2015
DOI: 10.1039/c4cp03822c
|View full text |Cite
|
Sign up to set email alerts
|

Packing and mobility of hydrocarbon chains in phospholipid lyotropic liquid crystalline lamellar phases and liposomes: characterisation by positron annihilation lifetime spectroscopy (PALS)

Abstract: Lipid lamellar mesophases and their colloidal dispersions (liposomes) are increasingly being deployed in vivo as drug delivery vehicles, and also as models of biological membranes in fundamental biophysics studies. The permeability and diffusion of small molecules such as drugs is accommodated by a change in local curvature and molecular packing (mesophase behaviour) of the bilayer membrane molecules. Positron annihilation lifetime spectroscopy (PALS) is capable of providing in situ molecular level information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…37 In the current work therefore we extend this hypothesis to include other structures and lipids of biophysical and/or pharmaceutical relevance. 37 In the current work therefore we extend this hypothesis to include other structures and lipids of biophysical and/or pharmaceutical relevance.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…37 In the current work therefore we extend this hypothesis to include other structures and lipids of biophysical and/or pharmaceutical relevance. 37 In the current work therefore we extend this hypothesis to include other structures and lipids of biophysical and/or pharmaceutical relevance.…”
Section: Introductionmentioning
confidence: 90%
“…11 The sensitivity of PALS to internal nanostructure has been investigated through comparison of oPs and I oPs of both the colloidal dispersions (cubosomes and hexosomes) and ''bulk'' mesophases. 37 Based upon the PALS lifetimes it may be anticipated that the diffusion of hydrophilic moieties from the colloidal dispersions would be more rapid than the ''bulk'' mesophase, which is reasonable given the greater surface area of these as nanoparticles. intravenous vs. depot) and several workers have shown that the nanostructure of the phase impacts upon the release profile of the drug.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…42 The overall structures (i.e. itself 56 and/or diffuse from one region to another 3 (Fig. 42,43 Cell membrane morphology is also controlled by the principles of amphiphile self assembly 52,53 and many of the non-lamellar architectures desribed in Fig.…”
Section: Fitting Pals Spectramentioning
confidence: 99%
“…Dong et al 56 have also compared the sensitivity of the PALS parameters to subtle changes in hydrocarbon packing arising from changes in chain mobility in liposomes, observing that there was no significant difference between the oPs lifetimes of some saturated and unsaturated lipids with C16 (DPPC vs. C 16:1 ) and C18 (DSPC vs. DOPC) chain length. 56 It was proposed that as the hydrophobic chains of the lipids exist in a highly mobile and disordered state within liposomes; this mobility outweighs any effect imposed by saturation.…”
Section: Pals: Influence Of Temperature and Chain Length On Membrane mentioning
confidence: 99%